Assessing upstream invasion risk in alien freshwater fishes based on intrinsic variations in swimming speed performance. Issue 1 (19th October 2015) - Starrs, Tyrie; Starrs, Danswell; Lintermans, Mark; Fulton, Christopher J.
Abstract: Managing the spread and impact of invasive species requires an understanding of what limits their dispersal into new areas. Here, we investigated an intrinsic component of invasive species dispersal, via assessments of the swimming speed performance of four species of alien freshwater fish at risk of invading the upper reaches of a montane river system in south‐east Australia. Using water flow measurements taken from a range of potential barriers to their upstream dispersal (fishways, culverts, natural riffle habitats), we assessed the likelihood of alien species passage based on intrinsic differences in swimming speed performance. With the four alien fish species displaying a wide range of sprint swimming speed ( U sprint ) capabilities, our logistic regression analysis identified pipe culverts as being a challenge to dispersal by all but the largest individuals of one species (Rainbow trout, Oncorhynchus mykiss ). Notably, fishway installations facilitating passage of the sympatric threatened species, Macquarie perch ( Macquaria australasica ), could allow upstream dispersal of a key threatening species (European perch, Perca fluviatilis ). Our study highlights the utility of locomotor capabilities for assessing the likelihood of upstream dispersal by species following human‐assisted introductions to the lower parts of a catchment.